Neonatal Abstinence Syndrome and Maternal Opioid-Related Diagnoses in the United States, 2010-2017. Issue 4 (December 2021) - Hirai, A.H.; Ko, J.Y.; Owens, P.L.; Stocks, C.; Patrick, S.W.
Abstract : ( JAMA . 2021;325:146–155) The rates of maternal opioid use disorder (OUD) and neonatal abstinence syndrome (NAS) in the United States rose substantially between 2000 and 2014. Opioid misuse and exposure can have adverse outcomes for both parturients and neonates. There are wide variations in the rates of NAS and maternal OUD in part due to an expansion in opioid-related disease identification codes in 2015. This study aimed to update estimated rates of NAS and maternal opioid-related diagnoses (MODs) in the United States, examine changes in rates since 2010, and describe variation in rates between states.